2020
DOI: 10.18502/ijdo.v12i1.3634
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resistance Training on G6Pase Gene Expression in Liver Hepatocytes, Glucose and Insulin Resistance Levels in Type 2 Diabetic Rats

Abstract: Objective: The aim of this study was to determine the effect of 12 weeks resistance training on G6Pase expression in liver cells, as well as glucose and insulin levels in type 2 diabetic rats. Materials and Methods: In this experimental study, 16 wistar rats were selected as the research sample. After injection of nicotinamide and streptozocin to induce diabetes, the rats were randomly divided into two groups of resistance training and control. The resistance group participated in a course of resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…In accordance with our results, earlier studies indicated an increase in liver Akt mRNA [ 55 ], and a decrease in PEPCK, and G6Pase following AT [ 54 , 56 ]. However, the underlying exercise-mediated mechanisms need to be elucidated, Akt signaling pathway regulates the expression of CREB and FoxO1 which may be associated with the expression of PEPCK and G6Pase [ 4 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our results, earlier studies indicated an increase in liver Akt mRNA [ 55 ], and a decrease in PEPCK, and G6Pase following AT [ 54 , 56 ]. However, the underlying exercise-mediated mechanisms need to be elucidated, Akt signaling pathway regulates the expression of CREB and FoxO1 which may be associated with the expression of PEPCK and G6Pase [ 4 , 57 ].…”
Section: Discussionsupporting
confidence: 93%